Rapidly screening of α-glucosidase inhibitors from Dioscorea opposita Thunb. peel based on rGO@Fe3O4 nanocomposites microreactor. (1st January 2018) - Zhang, Songsong; Qiu, Beibei; Zhu, Jinhua; Hu, Weiping; Ma, Fanyi; Khan, M. Z. H.; Liu, Xiuhua
Abstract: Present study aimed to immobilise the α-glucosidase on suitable supports to construct enzymatic microreactors and their subsequent applicability in efficient inhibitor screening from the Chinese Yam ( Dioscorea opposita Thunb.) peel. A type of lamellar and porous composites (rGO@Fe3 O4 ) were synthesised with a facile one-step solvothermal method and employed as carriers to construct enzymatic microreactors for screening α-glucosidase ligand from the Chinese Yam peel in league with the high performance liquid chromatography and mass spectrometry (HPLC-MS). The immobilisation amount of α-glucosidase on rGO@Fe3 O4 under the optimised conditions was about 40 μg α-glucosidase/mg carriers. Furthermore, the binding capacities of screened inhibitors, 2, 4-dimethoxy-6, 7-dihydroxyphenanthrene and batatasin I, were 35.6 and 68.2%, respectively. Hence, considering their high screening efficiency and excellent magnetic separation ability, these as-prepared nanocomposite consisting of rGO and Fe3 O4 may be potential supports for the enzyme (such as α-glucosidase) immobilisation for rapid α-glucosidase inhibitors screening from the diverse nature resources.